2021
DOI: 10.3389/fphys.2021.642117
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Score to Identify Super-Responders to Sacubitril/Valsartan in Ambulatory Patients With Heart Failure

Abstract: IntroductionSacubitril/valsartan (SV) promotes cardiac remodeling and improves prognosis in patients with heart failure (HF). However, the response to the drug may vary between patients and its implementation in daily clinical practice has been slower than expected. Our objective was to develop a score predicting the super-response to SV in HF outpatients.MethodsThis is a retrospective analysis of 185 consecutive patients prescribed SV from two tertiary hospitals between September 2016 and February 2018. Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…It has been reported that a shorter duration of disease is associated with a higher likelihood of recovery of LVEF ( 4 ). This result is also consistent with some prior reports ( 20 , 36 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It has been reported that a shorter duration of disease is associated with a higher likelihood of recovery of LVEF ( 4 ). This result is also consistent with some prior reports ( 20 , 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we also found that a single clinical index cannot predict LVRR well, which indicated that LVRR is a consequence of coaction of several factors. (20,36).…”
Section: Discussionmentioning
confidence: 99%
“…The criteria proposed in this paper are based on large registries evaluating biohumoral 5 or echocardiographic 23 effects of ARNI and have been used in other studies. 40 Furthermore, the response to treatment is also supported by CPET data, which had not been included in the preliminary established criteria of ARNI response in our study. Beyond ARNI, sodium‐glucose co‐transporter 2 inhibitors (SGLT2i) are known to reduce NT‐proBNP levels and improve cardiac function and prognosis.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, there is no univocal definition of ARNI efficacy. The criteria proposed in this paper are based on large registries evaluating biohumoral 5 or echocardiographic 23 effects of ARNI and have been used in other studies 40 . Furthermore, the response to treatment is also supported by CPET data, which had not been included in the preliminary established criteria of ARNI response in our study.…”
Section: Discussionmentioning
confidence: 94%
“…HF is characterized by cardiac remodeling, which includes the accumulation of compensatory structural and functional alterations to alleviate ventricular wall stress. 26 Autophagy occurs in hypoxic cells 27 and organs during cardiovascular diseases, such as HF, 28 suggesting its stimulation under ischemic conditions. The data of the present study showed that autophagy are activated following OGD exposure in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%